Critical religion: critical approaches to the study of religion (The Critical Religion Association, 2011)
"Critical Religion is a key marker of how we ‘do’ religion. Originating at the University of Stirling in Scotland, the term ‘critical religion’ seeks to describe two key approaches to thinking about religion"